The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1002/1097-4679(197204)28:2<230::aid-jclp2270280234>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential referral to significant others as a function of interpersonal effectiveness

Abstract: brief commentary on the usefulness of studying fears of snakes. J. abn. PsychoE. 1969,74,413-414. 3. LEVIS, D. J. The case for performing research on nonpatient populations with fears of small animals: a reply to Cooper, Furst, and Bridger. J. abn. Psychol., 1970, 76, 36-38. 4. MCGLYNN, F. D. Individual versus standardized hierarchies in the systematic desensitization of snake-avoidance. Behav. Res. Therapy, 1971, 9, 1-5. 5. MCGLYNN, F. D. and LINDER, L. H. The clinical application of analogue desensitization:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…If flexible thinking provides a foundation for empathic understanding, interventions oriented toward enhancing alternative social perspectives might prove useful. Interestingly, Pierce and Zarle (1972) reported that normal individuals who spontaneously referred more frequently to the thoughts and feelings of others during self-exploration were more interpersonally effective and had higher empathy scores. Hence, a goal of psychotherapeutic treatment could be to increase both the frequency and accuracy of the brain-injured patient’s reference to others.…”
Section: Discussionmentioning
confidence: 99%
“…If flexible thinking provides a foundation for empathic understanding, interventions oriented toward enhancing alternative social perspectives might prove useful. Interestingly, Pierce and Zarle (1972) reported that normal individuals who spontaneously referred more frequently to the thoughts and feelings of others during self-exploration were more interpersonally effective and had higher empathy scores. Hence, a goal of psychotherapeutic treatment could be to increase both the frequency and accuracy of the brain-injured patient’s reference to others.…”
Section: Discussionmentioning
confidence: 99%